From telling to sharing to silence: A longitudinal ethnography of professional‐patient communication about oral chemotherapy for colorectal cancer. Issue 2 (4th December 2018) - Mitchell, Gary; Porter, Sam; Manias, Elizabeth
Abstract: Background: Healthcare professionals are encouraged to promote concordance, a shared agreement about prescription and administration of medications, in their communication with patients. However, there is a paucity of research regarding the impact of communication about self‐administered oral chemotherapy. The aim of this study was to examine the changing dynamics of communication through the patient journey from diagnosis of colorectal cancer to posttreatment of chemotherapy. Methods: Over 60 hours of observational data were digitally recorded from interactions between 15 healthcare professionals, eight patients with colorectal cancer prescribed capecitabine, and 11 family members over a 6‐month period in outpatient departments within one hospital in the United Kingdom. Sixteen semi‐structured interviews were conducted with patients during and after their treatment. Three focus groups were carried out with healthcare professionals. These data were analysed using thematic analysis. Results: The patient journey followed a path of four distinct phases: autocracy, physiological concordance, holistic concordance, and silence. Initially, communication was medicalised with patients occupying a passive role. As patients continued their journey, they took a more active role in their treatment discussion by leading consultations and sharing their priorities of care. At the end of treatment, patients felt isolated and unsupported when they were discharged from their oncology team. Conclusions: Communication about oral chemotherapy is not a static process; it evolves to take account of changing clinical requirements and growing patient confidence in dealing with their cancer. Different stages in the treatment journey indicate the need for different approaches to communication.